Corporate Social Responsibility Disclosure and Financial Performance of Quoted Nigerian Cement Companies - Ibrahim Aliyu Gololo (International Business and Accounting Research Journal, 2019)
The issue of CSRD has been recognized as an evolving phenomenon since late 1970’s and it has been given attention in accounting literature with increased pressure from the stakeholders on companies to pay-back to their host communities. This study examines empirically the relationship between corporate social responsibility disclosure and financial performance of quoted cement companies in Nigeria. Secondary data were sourced and used from the quoted Nigerian cement companies annual reports. A Samples of three [3] companies emerged from the  population of five [5] companies using purposive sampling technique method. This study utilizes annual report of ten [10] years period covering [2008-2017] to obtain data for the study. The objective of this study is to examine relationship between CSRD and financial performance of quoted cement companies in Nigeria. Pooled OLS and Random Effect [RE] Panel Estimation analysis methods were used to display and discuss the results using STATA Version 12. The results revealed that corporate social responsibility disclosure have a significant and positive impact on the return on equity and return on capital employed. However, leverage and company size as control variables have a positive significant effects on the financial performance of quoted cement companies in Nigeria. Thus, CSRD is an important component to consider in determining financial performance of companies. The study recommends that quoted cement companies should increase the level of their CSR activities due to its enormous benefits on their financial performance, especially on the ROE and ROCE and Government should set quantum amount of atleast 2.5% on PBT of cement companies for execution of CSR activities to their immediate communities.